2017
DOI: 10.1002/pssa.201700709
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Curcumin Loaded Chitosan Nanoparticles for Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) is a minimally invasive tumor targeting strategy, in which tumor tissues can be selectively destroyed. Upon excitation with light of a specific wavelength, a photosensitizer can produce reactive oxygen species (ROS) in the presence of molecular oxygen, thereby exhibiting a cytotoxic effect toward the surrounding tissues, giving a total control on the onset of therapy. In this research work, curcumin as a natural photosensitizer has been investigated against cancer cells. To enhance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 23 publications
(18 reference statements)
0
30
0
Order By: Relevance
“…Despite its numerous therapeutic effects, the clinical benefits of curcumin are limited due to poor solubility, rapid metabolism, and systemic elimination of the native compound [24]. These limitations can be overcome by using different drug carriers to improve curcumin solubility [25][26][27]. Among such drug carriers, liposomes have been broadly studied showing promising therapeutic effects [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its numerous therapeutic effects, the clinical benefits of curcumin are limited due to poor solubility, rapid metabolism, and systemic elimination of the native compound [24]. These limitations can be overcome by using different drug carriers to improve curcumin solubility [25][26][27]. Among such drug carriers, liposomes have been broadly studied showing promising therapeutic effects [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…These limitations can be overcome by the use of polymeric nanoparticles such as carrier systems, wherein the active substance is protected from degradation in the physiological environment and the bio-membrane permeability and cellular uptake of highly hydrophobic molecules are facilitated [17]. Several studies have revealed a remarkable enhancement of curcumin’s phototoxicity through nanoparticle encapsulation [22,23,24,25,26]. One such polymer is PLGA, which is an FDA and European Medicines Agency (EMA) approved biocompatible and biodegradable polymer [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The surface morphology and size of NPs are critical physicochemical properties that affect biomedical functions [28]. The surface morphology and size of the simples produced via SEDS were characterized by SEM ( Figure 2).…”
Section: Surface Morphology and Particle Sizementioning
confidence: 99%